High-strength BOPA film and preparation method thereof

By adding modified Ti3C2Tx nanosheets and modified cashewol to the nylon 6 film, the shortcomings of existing nylon films in high-strength applications have been solved, the mechanical properties of the film have been significantly improved, and the needs of pharmaceutical packaging and large-load packaging are met.

CN119912808AActive Publication Date: 2025-05-02HUARUIDA PACKAGING LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510412828.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

Existing bidirectional tensile nylon films cannot meet actual needs in some high-strength application areas, such as pharmaceutical blister packaging and heavy object packaging that bears high load strength.

Method used

By adding modified Ti3C2Tx nanosheets and modified cashewol to the nylon 6 film, a high-strength BOPA film was prepared using a simple preparation method including mixing, melt extrusion, casting, bidirectional stretching and shaping.

Benefits of technology

The combination of modified Ti3C2Tx nanosheets and modified cashew pills significantly improves the mechanical properties of nylon films, including tensile strength, elongation at break and puncture resistance, meeting the needs of high-strength applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of nylon film preparation, in particular to a high-strength BOPA film and a preparation method thereof. The high-strength BOPA film is prepared from the following components in parts by weight: 75 to 92 parts of nylon 6, 5 to 20 parts of modified cardanol, 1 to 3 parts of a slipping agent, 0.5 to 1 part of a compatilizer, 0.5 to 1.5 parts of a dispersing agent and 1 to 5 parts of modified Ti3C2Tx nanosheets. The film has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nylon film preparation, in particular to a high-strength BOPA film and a preparation method thereof. Background Art

[0002] Biaxially oriented nylon film (BOPA) has the advantages of excellent heat resistance, chemical solvent resistance, light weight, low cost, and environmental protection. It is widely used in food, medicine, cosmetics, mechanical electronics and other packaging fields. At present, BOPA film is the third largest biaxially oriented flexible packaging material after biaxially oriented polypropylene film (BOPP) and biaxially oriented polyester film (BOPET). The polymer material used to prepare BOPA film is nylon 6 resin, which is a polymer with repeated amide groups on the main chain formed by the ring-opening polymerization of caprolactam.

[0003] With the economic development of my country and the improvement of people's quality of life, higher and higher requirements are put forward for the performance of packaging materials. Although biaxially oriented nylon film has good mechanical properties, it still cannot meet the actual application needs in some application fields, such as pharmaceutical blister packaging and heavy object packaging that requires high load strength. To this end, the present invention proposes a high-strength BOPA film and a preparation method thereof to solve the above-mentioned problems. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, one of the objects of the present invention is to provide a high-strength BOPA film having excellent mechanical properties.

[0005] The second object of the present invention is to provide a method for preparing a high-strength BOPA film, which has a simple preparation process.

[0006] One of the purposes of the present invention is achieved by the following technical solution: A high-strength BOPA film, which comprises, by weight, 75-92 parts of nylon 6, 5-20 parts of modified cardanol, 1-3 parts of a lubricant, 0.5-1 parts of a compatibilizer, 0.5-1.5 parts of a dispersant, and 15 parts of modified Ti3C2T x Nanosheets.

[0007] Furthermore, the modified Ti3C2T x The preparation method of the nanosheets is as follows: (1) Ti3C2T x Nanosheets, 4-bromoaniline, and isoamyl nitrite were mixed and stirred to react, and bromobenzene-Ti3C2T was obtained after purification. x Nanosheets; (2) Replacing the bromobenzene-Ti3C2T xNanosheets, tetrakis(triphenylphosphine)palladium, and cuprous iodide were added to a mixed solution of toluene and triethylamine, stirred for 1-1.5 h, and then 1,3,5-triethynylbenzene and 1,4-dibromobenzene were added to react. The modified Ti3C2T x Nanosheets.

[0008] Furthermore, the cuprous iodide, tetrakis(triphenylphosphine)palladium, bromobenzene-Ti3C2T x The mass ratio of the nanosheets, 1,3,5-triethynylbenzene and 1,4-dibromobenzene is 1:(5-6):(9-11):(3-5):(12-15); the volume ratio of toluene and triethylamine is 1:1; the reaction temperature is 95-110°C and the reaction time is 68-76h.

[0009] Furthermore, the isopentyl nitrite, Ti3C2T x The dosage ratio of the nanosheets and 4-bromoaniline is 1 mL: (25-35) mg: (550-600) mg; the stirring reaction temperature is 55-65° C., and the stirring reaction time is 8-10 hours.

[0010] Furthermore, in step (1), the Ti3C2T x The preparation method of the nanosheets is as follows: according to the dosage ratio of LiF, Ti3AlC2 powder and hydrochloric acid being 1g: (0.5-1)g: (8-15)mL; LiF is added to the hydrochloric acid solution, and then Ti3AlC2 powder is added for etching, and a precipitate is obtained after centrifugation, and Ti3C2T is obtained by ultrasonic stratification and purification. x Nanosheets; the concentration of the hydrochloric acid is 5-10 mol / L; the etching temperature is 40-55° C., and the etching time is 36-48 h.

[0011] Furthermore, the preparation method of the modified cardanol is as follows: The purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are reacted to obtain modified cardanol after purification.

[0012] Furthermore, the purification process of the purified cardanol is as follows: cashew nut oil and a small amount of zeolite are mixed and subjected to reduced pressure distillation, low-boiling point substances below 200° C. are collected, and then a fraction of 200-240° C. is collected under a vacuum degree of 1000 Pa.

[0013] Furthermore, the molar ratio of the purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1:(0.2-0.5):(0.5-1); the reaction temperature is 80-95° C., and the reaction time is 1-2 h.

[0014] Furthermore, the lubricant is one or more of oleic acid amide, silicone oil, and polyethylene wax; the compatibilizer is one or two of ethylene-acrylic acid copolymer and epoxy resin; and the dispersant is silicon dioxide.

[0015] The second object of the present invention is achieved by adopting the following technical solution: The method for preparing the above-mentioned high-strength BOPA film comprises the following steps: According to the weight proportions, nylon 6, modified cardanol, lubricant, compatibilizer, dispersant and modified Ti3C2T x The nanosheets are mixed uniformly to obtain a premix; the premix is ​​melt-extruded, cast, biaxially stretched, and shaped.

[0016] Furthermore, the temperature of the biaxial stretching is 150-170°C; the ratio of the biaxial stretching is (2.5×2.5)-(3.5×3.5); and the setting temperature is 160-180°C.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The high-strength BOPA film of the present invention is added with modified Ti3C2T x Nanosheets, modified cardanol and other raw materials, the combination of the two can improve the overall mechanical properties of nylon film. Specifically, modified Ti3C2T x The nanosheets are prepared by using amino-containing 4-bromoaniline and Ti3C2T x The hydroxyl groups on the nanosheets reacted to obtain bromobenzene-modified Ti3C2T x The nanosheets were then grafted onto bromobenzene-modified Ti3C2T4 nanosheets using the Sonogashira–Hagihara reaction to polymerize 1,3,5-triethynylbenzene and 1,4-dibromobenzene. x Modified Ti3C2T x The presence of negatively charged hydrophilic functional groups (such as -OH, -O and -F) on the surface of the nanosheets can form strong electrostatic interactions or hydrogen bonds with the main chain of nylon 6 to improve its compatibility and dispersibility, making the modified Ti3C2T x Nanosheets can effectively transfer stress, thereby improving the mechanical properties of the film; on the other hand, the modified Ti3C2T xThe high rigidity skeleton of the conjugated polymer grafted on the surface of the nanosheet also gives the nylon film a higher tensile strength. Modified cardanol is synthesized in one step using cardanol, terminal amino tetramethyl disiloxane and polyformaldehyde as raw materials using the Mannich reaction. The long-chain carbon structure and tetramethyl disiloxane structure contained in the modified cardanol can give the nylon film better flexibility, thereby enhancing the mechanical properties of the nylon film. The experimental results show that the tensile strength of the BOPA film of the present invention is above 323MPa (MD) and 328MPa (TD); the elongation at break of the BOPA film is above 149% (MD) and 151% (TD); the puncture resistance of the BOPA film is above 22.8N. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0019] The preparation process of purified cardanol in the embodiment is as follows: In a 500mL three-necked flask equipped with N2 protection, a condenser, a thermometer and a magnetic rotor, add 250g of cashew nut oil and a small amount of zeolite, insert a thermistor thermometer into the left bottle mouth to control the solution temperature, and use a vacuum oil pump for reduced pressure distillation. First, collect low-boiling point substances below 200°C, then replace the condensation receiving device, and collect the 200-240°C fraction under a vacuum degree of 1000Pa to obtain purified cardanol.

[0020] 1. Implementation Example 1 A high-strength BOPA film, which is composed of 80 parts of nylon 6, 12 parts of modified cardanol, 2 parts of oleic acid amide, 0.7 parts of ethylene-acrylic acid copolymer, 1.1 parts of silicon dioxide, and 2 parts of modified Ti3C2T x Nanosheet composition.

[0021] Among them, modified Ti3C2T x The preparation process of nanosheets is as follows: (1) According to the dosage ratio of LiF, Ti3AlC2 powder and hydrochloric acid of 1g:0.7g:12mL, LiF was added to 8mol / L hydrochloric acid solution, and Ti3AlC2 powder was added. The solution was etched at 50°C for 40h, and a precipitate was obtained after centrifugation. The precipitate was washed until the pH was neutral, and multilayer Ti3C2T was obtained after filtration. x Nanosheets, multilayer Ti3C2T xThe nanosheets were added to deionized water, ultrasonically separated at 450 W for 0.5 h, centrifuged at 3500 rpm for 8 min, and freeze-dried at -50 °C for 36 h to obtain Ti3C2T x Nanosheets; According to isoamyl nitrite, Ti3C2T x The dosage ratio of nanosheets and 4-bromoaniline was 1 mL: 30 mg: 580 mg. x Nanosheets and 4-bromoaniline were mixed, and then isoamyl nitrite was slowly added. The mixture was stirred at 60 °C for 9 h. After the reaction was completed, DMF was added to the reaction solution, and the solid precipitate was collected by filtration. The solid precipitate was washed with DMF until the filtrate became colorless, and then washed with methanol to remove DMF. The precipitate was dried in vacuo to obtain bromobenzene-Ti3C2T x Nanosheets.

[0022] (2) According to cuprous iodide, tetrakis(triphenylphosphine)palladium, bromobenzene-Ti3C2T x The mass ratio of nanosheets, 1,3,5-triethynylbenzene and 1,4-dibromobenzene is 1:5.6:10:4:13. The bromobenzene-Ti3C2T x Nanosheets, tetrakis(triphenylphosphine)palladium, and cuprous iodide were added to a mixed solution of toluene and triethylamine (1:1, v / v) and stirred for 1.2 h. Then 1,3,5-triethynylbenzene and 1,4-dibromobenzene were added and reacted at 100 °C for 70 h. The product was collected by filtration and washed with acetone, methanol, dichloromethane, and ether in turn. Then, the product was dried in vacuo to obtain modified Ti3C2T x Nanosheets.

[0023] The preparation process of modified cardanol is as follows: According to the mass ratio of purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane being 1:0.4:0.8, the purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are added into a four-necked flask equipped with a stirring rod, a thermometer and a condensing reflux tube, stirred evenly at a speed of 60 rpm, reacted at 90°C for 1.5h, water was separated by vacuum distillation, and then cooled to room temperature to obtain the product.

[0024] The preparation method of the above-mentioned high-strength BOPA film is as follows: According to the weight proportions, nylon 6, modified cardanol, oleic acid amide, ethylene-acrylic acid copolymer, silicon dioxide and modified Ti3C2T xThe nanosheets are mixed uniformly to prepare a premix; the premix is ​​added to a twin-screw extruder, and the processing temperature of each zone of the twin-screw extruder is set to 240°C, and a masterbatch is obtained by melt extrusion granulation; the masterbatch is added to a casting machine for extrusion casting, and then the cast sheet is biaxially stretched at 160°C and a ratio of 3×3, and then shaped at 170°C.

[0025] Example 2 A high-strength BOPA film, which is composed of 75 parts of nylon 6, 5 parts of modified cardanol, 1 part of a mixture of oleic acid amide and silicone oil (the ratio of the two is 1:1), 0.5 parts of epoxy resin, 0.5 parts of silicon dioxide, and 1 part of modified Ti3C2T x Nanosheet composition.

[0026] Among them, modified Ti3C2T x The preparation process of nanosheets is as follows: (1) According to the dosage ratio of LiF, Ti3AlC2 powder and hydrochloric acid of 1g:0.5g:8mL, LiF was added to 5mol / L hydrochloric acid solution, and Ti3AlC2 powder was added. The solution was etched at 40°C for 48h. The precipitate was obtained after centrifugation. The precipitate was washed until the pH was neutral and filtered to obtain multilayer Ti3C2T x Nanosheets, multilayer Ti3C2T x The nanosheets were added to deionized water, ultrasonically separated at 450 W for 0.5 h, centrifuged at 3500 rpm for 8 min, and freeze-dried at -50 °C for 36 h to obtain Ti3C2T x Nanosheets; According to isoamyl nitrite, Ti3C2T x The dosage ratio of nanosheets and 4-bromoaniline was 1 mL: 25 mg: 550 mg. x Nanosheets and 4-bromoaniline were mixed, and then isoamyl nitrite was slowly added. The mixture was stirred at 55 °C for 10 h. After the reaction was completed, DMF was added to the reaction solution. The solid precipitate was collected by filtration and washed with DMF until the filtrate became colorless. Then, it was washed with methanol to remove DMF and dried in vacuum to obtain bromobenzene-Ti3C2T x Nanosheets.

[0027] (2) According to cuprous iodide, tetrakis(triphenylphosphine)palladium, bromobenzene-Ti3C2T x The mass ratio of nanosheets, 1,3,5-triethynylbenzene and 1,4-dibromobenzene is 1:5:9:5:12. The bromobenzene-Ti3C2T xNanosheets, tetrakis(triphenylphosphine)palladium, and cuprous iodide were added to a mixed solution of toluene and triethylamine (1:1, v / v) and stirred for 1 h. Then 1,3,5-triethynylbenzene and 1,4-dibromobenzene were added and reacted at 95 °C for 76 h. The product was collected by filtration and washed with acetone, methanol, dichloromethane, and ether in turn. The product was dried in vacuo to obtain modified Ti3C2T x Nanosheets.

[0028] The preparation process of modified cardanol is as follows: According to the mass ratio of purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane being 1:0.5:1, the purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are added into a four-necked flask equipped with a stirring rod, a thermometer and a condensing reflux tube, stirred evenly at a speed of 60 rpm, reacted at 80°C for 2h, separated out water by vacuum distillation, and then cooled to room temperature to obtain the product.

[0029] The preparation method of the above-mentioned high-strength BOPA film is as follows: According to the weight proportions, nylon 6, modified cardanol, oleic acid amide and silicone oil mixture, epoxy resin, silicon dioxide and modified Ti3C2T x The nanosheets are mixed uniformly to prepare a premix; the premix is ​​added to a twin-screw extruder, and the processing temperature of each zone of the twin-screw extruder is set to 240°C, and a masterbatch is obtained by melt extrusion granulation; the masterbatch is added to a casting machine for extrusion casting, and then the cast sheet is biaxially stretched at 150°C and a ratio of 3.5×3.5, and then shaped at 160°C.

[0030] Example 3 A high-strength BOPA film, which is composed of 92 parts of nylon 6, 5-20 parts of modified cardanol, 3 parts of a mixture of oleic acid amide, silicone oil, and polyethylene wax (mixed in a ratio of 1:1:1), 1 part of a mixture of ethylene-acrylic acid copolymer and epoxy resin (mixed in a ratio of 1:1), 1.5 parts of silicon dioxide, 5 parts of modified Ti3C2T x Nanosheet composition.

[0031] Among them, modified Ti3C2T x The preparation process of nanosheets is as follows: (1) According to the dosage ratio of LiF, Ti3AlC2 powder and hydrochloric acid of 1g:1g:15mL, LiF was added to a 10mol / L hydrochloric acid solution, and Ti3AlC2 powder was added. The solution was etched at 55°C for 36h. The precipitate was obtained after centrifugation. The precipitate was washed until the pH was neutral and filtered to obtain multilayer Ti3C2T x Nanosheets, multilayer Ti3C2T xThe nanosheets were added to deionized water, ultrasonically separated at 450W for 0.5h, then centrifuged at 3500rpm for 8min, and then freeze-dried at -50℃ for 36h to obtain Ti3C2Tx nanosheets. x The dosage ratio of nanosheets and 4-bromoaniline was 1 mL: 35 mg: 600 mg. x Nanosheets and 4-bromoaniline were mixed, and then isoamyl nitrite was slowly added. The mixture was stirred at 65 °C for 8 h. After the reaction was completed, DMF was added to the reaction solution. The solid precipitate was collected by filtration and washed with DMF until the filtrate became colorless. Then, it was washed with methanol to remove DMF and dried in vacuum to obtain bromobenzene-Ti3C2T x Nanosheets.

[0032] (2) According to cuprous iodide, tetrakis(triphenylphosphine)palladium, bromobenzene-Ti3C2T x The mass ratio of nanosheets, 1,3,5-triethynylbenzene and 1,4-dibromobenzene is 1:6:11:7:15. The bromobenzene-Ti3C2T x Nanosheets, tetrakis(triphenylphosphine)palladium, and cuprous iodide were added to a mixed solution of toluene and triethylamine (1:1, v / v) and stirred for 1.5 h. Then 1,3,5-triethynylbenzene and 1,4-dibromobenzene were added and reacted at 110 °C for 68 h. The product was collected by filtration and washed with acetone, methanol, dichloromethane, and ether in turn. Then, the product was dried in vacuo to obtain modified Ti3C2T x Nanosheets.

[0033] The preparation process of modified cardanol is as follows: According to the mass ratio of purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane being 1:0.2:0.5, the purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are added into a four-necked flask equipped with a stirring rod, a thermometer and a condensing reflux tube, stirred evenly at a speed of 60 rpm, reacted at 95°C for 1 hour, separated out water by vacuum distillation, and then cooled to room temperature to obtain the product.

[0034] The preparation method of the above-mentioned high-strength BOPA film is as follows: According to the weight proportions, nylon 6, modified cardanol, oleic acid amide, silicone oil, a mixture of polyethylene wax, ethylene-acrylic acid copolymer, epoxy resin, silicon dioxide and modified Ti3C2T xThe nanosheets are mixed uniformly to prepare a premix; the premix is ​​added to a twin-screw extruder, and the processing temperature of each zone of the twin-screw extruder is set to 240°C, and a masterbatch is obtained by melt extrusion granulation; the masterbatch is then added to a casting machine for extrusion casting, and the cast sheet is biaxially stretched at 170°C and a ratio of 2.5×2.5, and then shaped at 180°C.

[0035] (II) Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Ti3C2T x Nanosheets instead of modified Ti3C2T x Nanosheets, and the rest are the same as in Example 1.

[0036] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the modified cardanol is omitted, and the rest is the same as Example 1.

[0037] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that purified cardanol and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are used instead of modified cardanol, the molar ratio of purified cardanol and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1:0.9, and the rest is the same as Example 1.

[0038] (III) Experimental examples The properties of the films obtained in Examples 1-3 and Comparative Examples 1-3 were tested, and the specific testing methods are as follows: Tensile strength and elongation at break: Tested in accordance with the experimental conditions for films and sheets in Part 3 of GB / T1040.3-2006. Each sample was repeated 5 times. The experimental results are the average of the 5 repeated tests. The experimental results are shown in Table 1. Puncture resistance: GB / T 20218-2021 "Biaxially oriented polyamide (nylon) film" tests the puncture resistance of the sample. Each sample is repeated 5 times. The experimental results are the average of 5 repeated experiments. The experimental results are shown in Table 1.

[0039] Table 1 As shown in Table 1, the films prepared in Examples 1-3 have excellent mechanical properties. x Nanosheets instead of modified Ti3C2T x Nanosheets, comparative example 2 omitted modified cardanol, and comparative example 3 used purified cardanol and 1,3-bis(3-aminopropyl)tetramethyldisiloxane instead of modified cardanol, all of which resulted in reduced mechanical properties of the prepared films. xThe presence of negatively charged hydrophilic functional groups (such as -OH, -O and -F) on the surface of the nanosheets can form strong electrostatic interactions or hydrogen bonds with the main chain of nylon 6 to improve its compatibility and dispersibility; on the other hand, the high rigidity skeleton structure of the conjugated microporous polymer grafted on its surface gives the nylon film higher tensile strength and puncture resistance. The combined effect of the long-chain carbon structure and tetramethyldisiloxane structure contained in the modified cardanol gives the nylon film better flexibility, thereby improving the mechanical properties of the nylon film. In summary, the modified Ti3C2T x The combination of nanosheets and modified cardanol can improve the overall mechanical properties of nylon film.

[0040] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A high-strength BOPA film, characterized in that: In parts by weight, the high-strength BOPA film comprises: 75-92 parts of nylon 6, 5-20 parts of modified cardanol, 1-3 parts of lubricant, 0.5-1 parts of compatibilizer, 0.5-1.5 parts of dispersant, 1-5 parts of modified Ti3C2T x Nanosheets.

2. The high-strength BOPA film according to claim 1, characterized in that: The modified Ti3C2T x The preparation method of the nanosheets is as follows: (1) Ti3C2T x Nanosheets, 4-bromoaniline, and isoamyl nitrite were mixed and stirred to react, and bromobenzene-Ti3C2T was obtained after purification. x Nanosheets; (2) Replacing the bromobenzene-Ti3C2T x Nanosheets, tetrakis(triphenylphosphine)palladium, and cuprous iodide were added to a mixed solution of toluene and triethylamine, stirred for 1-1.5 h, and then 1,3,5-triethynylbenzene and 1,4-dibromobenzene were added to react. The modified Ti3C2T x Nanosheets.

3. The high-strength BOPA film according to claim 2, characterized in that: The cuprous iodide, tetrakis(triphenylphosphine)palladium, bromobenzene-Ti3C2T3 x The mass ratio of the nanosheets, 1,3,5-triethynylbenzene and 1,4-dibromobenzene is 1:(5-6):(9-11):(3-5):(12-15); the volume ratio of toluene and triethylamine is 1:1; the reaction temperature is 95-110°C and the reaction time is 68-76h.

4. The high-strength BOPA film according to claim 2, characterized in that: The isopentyl nitrite, Ti3C2T x The dosage ratio of the nanosheets and 4-bromoaniline is 1 mL: (25-35) mg: (550-600) mg; the stirring reaction temperature is 55-65° C., and the stirring reaction time is 8-10 hours.

5. The high-strength BOPA film according to claim 2, characterized in that: Ti3C2T in step (1) x The preparation method of the nanosheets is as follows: according to the dosage ratio of LiF, Ti3AlC2 powder and hydrochloric acid being 1g: (0.5-1)g: (8-15)mL; LiF is added to the hydrochloric acid solution, and then Ti3AlC2 powder is added for etching, and a precipitate is obtained after centrifugation, and Ti3C2T is obtained by ultrasonic stratification and purification. x Nanosheets; the concentration of the hydrochloric acid is 5-10 mol / L; the etching temperature is 40-55° C., and the etching time is 36-48 h.

6. The high-strength BOPA film according to claim 1, characterized in that: The preparation method of the modified cardanol is as follows: The purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are reacted to obtain modified cardanol after purification.

7. The high-strength BOPA film according to claim 1, characterized in that: The mass ratio of the purified cardanol, polyformaldehyde and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1:(0.2-0.5):(0.5-1); the reaction temperature is 80-95° C. and the reaction time is 1-2 hours.

8. The high-strength BOPA film according to claim 1, characterized in that: The lubricant is one or more of oleic acid amide, silicone oil and polyethylene wax; the compatibilizer is one or two of ethylene-acrylic acid copolymer and epoxy resin; and the dispersant is silicon dioxide.

9. The method for preparing the high-strength BOPA film according to claim 1, characterized in that: The following steps are involved: According to the weight proportions, nylon 6, modified cardanol, lubricant, compatibilizer, dispersant and modified Ti3C2T x The nanosheets are mixed uniformly to obtain a premix; the premix is ​​melt-extruded, cast, biaxially stretched, and shaped.

10. The method for preparing the high-strength BOPA film according to claim 9, characterized in that: The temperature of the biaxial stretching is 150-170°C; the ratio of the biaxial stretching is (2.5×2.5)-(3.5×3.5); and the setting temperature is 160-180°C.

Citation Information

Patent Citations

  • High-wear-resistance MC nylon / MXene nano composite material and in-situ polymerization preparation method thereof

    CN111072952A

  • Lightweight high-toughness military shelter structural adhesive and preparation method thereof

    CN111876118A

  • Preparation method of high-adhesion and high-wear-resistance lightweight nylon powder

    CN115819788A

  • Conductive composite material

    CN116195007A

  • High-toughness wear-resistant laminated board and preparation method thereof

    CN116985484A